PETROPHYSICAL EVALUATION OF THE UPPER QISHN CLASTIC RESERVOIR IN SHARYOOF OILFIELD, SAYUN-MASILAH BASIN, YEMEN - Abdullah, E.A. (Asian Research Publishing Network, 2021)
The underneath Upper Qishn clastic sediments, which they revealed in the Sharyoof oilfield have been perfectly investigated. The Upper Qishn clastic reservoir petrophysical properties such as the saturation and porosity were evaluated utilizing well logs data. The findings were used to assess the importance of the reservoir and hydrocarbon capacity. The Upper Qishn Clasty lithology has been estimated utilizing well logs, which they infer that the lithofacies of this interval consists mainly of carbonate, sandstone, and low-shale intercalation. The wireline logging data had been carefully evaluated during the processing of the data; therefore, data quality was thought to be good. The findings from the porosity reservoir tested for six wells indicate an overall average porosity of 14.62 to 24.2, while the relative permeability is 11.98 to 18.2. Nevertheless, the water saturation of the reservoir varies from about 50 to 84.1. Saturation of hydrocarbons, on the other hand, is in reverse relation to saturation of water. Based on the on these investigated outcomes, this reservoir interval is interpreted as an excellent reservoir with high median of efficient porosity reach to 20 and high hydrocarbon above 50 . The Upper Qishn clastic reservoir demonstrates excellent potential of the reservoir, particularly the topmost reservoir component to be properly considered in upcoming oilfield development. In the Upper Qishn clastic reservoir, the hydrocarbon saturation map shows an ordinary distribution pattern, with an overall rise to the north - west, and east direction, as they decrease into southwestern wards. Â© 2006-2021 Asian Research Publishing Network (ARPN). All rights reserved.